Synthesis of vitamin E and aliphatic lipid vanadium(IV) and (V) complexes, and their cytotoxic properties - Hadjiadamou, Ioanna; Vlasiou, Manolis; Spanou, Smaragda; Simos, Yannis; Papanastasiou, George; Kontargiris, Evangelos; Dhima, Irida; Ragos, Vasilios; Karkabounas, Spyridon; Drouza, Chryssoula; Keramidas, Anastasios D. (My University, 2020)
Novel vitamin E chelate derivatives and their VIV/V complexes have been synthesized and characterized, and their anticancer properties have been evaluated. The new complexes have been designed to exhibit enhanced cytotoxicity by combining high lipophilicity with the properties of vanadium to induce the formation of reactive oxygen species (ROS). In particular, the β-tocopherol derivatives with iminodiethanol (β-tocDEA) and dipicolylamine (β-tocDPA) as well their VV and VIV complexes, [VVO(β-tocDEA] and [VIVO(β-tocDPA] have been synthesized and characterized by Nuclear Magnetic Resonance (NMR), Ultra Violet-Visible (UV–Vis) and Electron Paramagnetic Resonance (EPR) spectroscopies. Although the β-tocopherol compounds exhibit antioxidant activity their complexes induce formation of radicals. In addition, two vanadium amphiphilic complexes of 2,2′-((2-hydroxyoctadecyl)azanediyl)bis(ethan-1-ol) (C18DEA) and 1-(bis(pyridin-2-ylmethyl)amino)octadecan-2-ol (C18DPA) known to activate O2 and produce ROS were synthesized and characterized (C. Drouza, A. Dieronitou, I. Hadjiadamou, M. Stylianou, J. Agric. Food. Chem., vol. 65, 2017, pp. 4942–4951). The four amphiphilic vanadium complexes exhibit enhanced hydrolytic stability. All compounds found to be cytotoxic for cancer cells exhibiting activity similar or higher to cis-platin.
Keywords: Cytotoxic; Radicals; Tocopherol; Vanadium; Vitamin E